Final answer:
To solve the equation (1x - 2)(1923)(9x + 1) and find the value of x, expand the expression, simplify, and use the quadratic formula to solve for x.
Step-by-step explanation:
To solve the equation (1x - 2)(1923)(9x + 1) and find the value of x, we can expand the expression and simplify:
(1x - 2)(1923)(9x + 1) = (1923x - 3846)(9x + 1) = 17307x² - 15330x - 3846
Now, set the equation equal to 0 and solve for x using the quadratic formula:
17307x² - 15330x - 3846 = 0
x = (-b ± √(b² - 4ac)) / (2a) = (-(-15330) ± √((-15330)² - 4(17307)(-3846))) / (2(17307))
x ≈ -1 or x ≈ 0.222
Therefore, the possible values of x are approximately x = -1 or x = 0.222